Racism, Muslims and the national imagination - Kyriakides, Christopher; Virdee, Satnam K.; Modood, Tariq (My University, 2009)
This qualitative study investigates the relationship between racism and nationalism in two multi-ethnic British neighbourhoods, focusing specifically on the construction of ‘the Muslim’ as a racialised role sign. Through in-depth interviews with 102 ‘white’ and ‘non-white’ participants in Glasgow (Scotland) and Bristol (England) we investigate the extent to which ‘the Muslim’ is being demonised as an oppositional identity in the construction of English and Scottish codes of cultural belonging. We find that whilst Scottishness and Englishness draw on historically founded racialised (e.g. biological, phenotypical) referents of ‘whiteness’ at the level of the ‘multi-ethnic’ neighbourhood, such racialised codes of belonging are undermined in everyday life by hybridised codes: signifiers such as accent, dress, mannerisms and behaviours which destabilise phenotype as a concrete signifier of national belonging. However, those signifiers that contest the racialised referent are themselves reconfigured, such that contemporary signifiers of cultural values (e.g. terrorist, extremist) reinforce, but not completely, the original racialised referent. We conclude that a negative view of ‘the Muslim’ as antithetical to imagined racialised conceptions of nationhood cannot easily be sustained in the Scottish and English ‘multi-ethnic’ neighbourhood. The sign ‘Muslim’ is split such that contemporary significations perpetuate the exclusion of the ‘unhybridised foreign Muslim’.
Keywords: Ethnic identity; Fundamentalism; Muslims; Nationalism; Racism; Cultural identity